Israel and the Assyrians: Deuteronomy, the Succession Treaty of Esarhaddon, and the Nature of Subversion - Crouch, C.L. (SBL, 2014)
Crouch focuses on Deuteronomy’s subversive intent, asking what would be required in order for Deuteronomy to successfully subvert either a specific Assyrian source or Assyrian ideology more generally. The book reconsiders the nature of the relationship between Deuteronomy and Assyria, Deuteronomy’s relationship to ancient Near Eastern and biblical treaty and loyalty oath traditions, and the relevance of Deuteronomy’s treaty affinities to discussions of its date.